Parathyroid Hormone-25(OH)D and Calcium-Phosphorus Ratio as Osteopenia Risk Factors in Women with Central Obesity - Meita Hendrianingtyas; Banundari Rachmawati; Ignatius Riwanto; Budi Mulyono; Suhartono Suhartono; Tri Indah Winarni; Lisyani Budipardigdo Suromo (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Central obesity has a close association with inflammation and the state of bone mass. Osteopenia is an abnormal condition of bone density. Bone mass density is influenced by several factors, such as 25(OH)D, parathyroid hormone (PTH), calcium (Ca) and phosphorus (P). The aim of this study was to evaluate the role of PTH-25(OH)D and Ca-P ratio as risk factors for osteopenia in women with central obesity.METHODS: A cross-sectional study was conducted in September 2020 to March 2021. The total subjects were 130 women aged 25-50 years old with central obesity. The diagnosis of osteopenia was done using dual X-ray absorptiometry (DXA) to measure bone mineral density. Enzyme linked fluorescent assay (ELFA) method was done to measure PTH and 25(OH)D levels, ion selective electrode method to measure Ca, and photometer method to measure P level. The receiver operating characteristic (ROC) curve was used to determine the optimal cut-off value and calculated prevalence ratio (PR) for osteopenia risks, followed by logistic regression analysis.RESULTS: The PR of PTH level was 10.18 (95% CI: 1.15–5.85; p=0.01); the PTH-25(OH)D ratio was 5.12 (95% CI: 1.13–23.19; p=0.04); Ca level was 6.0 (95% CI: 1.33–27.14; p=0.02) and Ca-P ratio was 4.89 (95%CI: 1.33–17.97; p=0.02). The PR for PTH together with Ca level was 18.71 (95% CI: 2.17–160.40; p=0.008).CONCLUSION: The PTH-25(OH)D ratio and the Ca-P ratio are risk factors for the incidence of osteopenia in women with central obesity. A high PTH-25(OH)D ratio and a high Ca-P ratio would have a higher risk of developing osteopenia in this population.KEYWORDS: CRP, PTH-25(OH)D, Ca-P, osteopenia, central obesity, women